Teori Permintaan Dan Konsumsi Inter-Temporal Antara Islam Dan Konvensional - Mochammad Afif (JES (Jurnal Ekonomi Syariah), 2017)
Islamic economic view on demand and consumption is relatively equal with conventional economics, but there are limits for individual to behave economically in accordance with the rules of sharia. In Islamic economics, Islamic norms and morals, which are Islamic principles in conducting economic activities, are factors that determine an individual or society in conducting economic activities, so that Islamic economic theory is different from the theory of conventional economics. Demand is from the consumer and supply is from producer. Both of these are central to an economic problem because these two things make market work. Therefore, before looking at whether policy or event is capable of affecting the economy, we must first see the effect on demand and supply, including The object of discussion is the issue of inter-temporal consumption, that is consumption executed in two times, namely the present (first period) and the future (second period). Instruments that may affect the volume of money are allocated for consumption in either the first or second period includ: First, Zakah; the imposition of zakat in the first period 1 (Z1)) will reduce m1 allocated to C1. If there is no savings or lending in the first period, then final spending (m1 = FS = C1 +Z1) is same with m1. Second, Infaq or shadaqah; the expenditure of infaq or shadaqah in the first period will reduce the m1 allocated to C1. There is no savings or lending in the first period, then final spending equals m1. Third, rate of profit or profit sharing (rp); if in the first period there is a portion of m1 allocated in the form of savings and is invested, then the final spending the second period (FS2) equals m2 the number of m1 saved is added with the rate of profit (rp) (FS2 = m2 + (1 + rp) m1 ). Keywords: Inter-temporal, Consumption, Demand, Islam, Conventional